Unconventional monetary policy - Central Bank of Nigeria, Research Department (Abuja, Nigeria Central Bank of Nigeria., 2016)
Discusses the nature and features of unconventional monetary policy and shows how it has been implemented in Nigeria.
Includes bibliographical references.
oif 01/06/17
Ref.
Keywords: Monetary policy; Macroeconomics